Could the Boom‐Bust in the Eurozone Periphery Have Been Prevented?. (31st October 2018) - Bielecki, Marcin; Brzoza‐Brzezina, Michał; Kolasa, Marcin; Makarski, Krzysztof
Abstract: Boom‐bust cycles in the eurozone periphery almost toppled the single currency and recent experience suggests that they may return soon. We check whether monetary or macroprudential policy could have prevented the periphery's violent boom and bust after the euro adoption. We estimate a DSGE model for the two euro area regions, core and periphery, and conduct a series of historical counterfactual experiments in which monetary and macroprudential policy follow optimized rules that use area‐wide welfare as the criterion. We show that single monetary policy could have better stabilized output in both regions, but not the housing market or the periphery's trade balance. In contrast, region‐specific macroprudential policy could have substantially smoothed the credit cycle in the periphery and reduced the build‐up of external imbalances.